Rapid scavenging of methylene blue dye from a liquid phase by adsorption on alumina nanoparticles - Banerjee S.; Gautam R.K.; Jaiswal A.; Chattopadhyaya M.C.; Sharma Y.C. (My University, 2025)
The adsorption behavior of methylene blue on as-synthesized alumina nanoparticles has been investigated. The adsorbent was characterized by Fourier transform infrared spectroscopy (FTIR), TG/DTA/DTG, X-ray diffractrometry and scanning electron microscopy. N2 adsorption-desorption measurements were carried out to analyze the porous structure and surface area of the adsorbent and results revealed that the adsorbent is mesoporous with a specific surface area of 76 m2 g-1. Batch experiments indicated that solution pH, initial dye concentration, contact time, temperature and the presence of ions had prominent impact on the dye removal process. The sorption kinetic data were found to be in accordance with pseudo-second order kinetics. The mechanistic interaction of the adsorbate-adsorbent system was also interpreted with the help of Weber-Morris model and the Boyd model and it was found that the adsorption process is controlled by a film diffusion mechanism. The investigation of adsorption isotherms suggested that the data fitted Langmuir isotherm model. The values the thermodynamic parameters for the process of removal were determined and the negative values change in free energy, ΔG0, indicated the spontaneous nature of the sorption process. A high desorption efficiency of 90.11% indicated a possible regeneration of the adsorbent. The adsorbent displayed almost the same adsorption capacity even after three cycles of regeneration bringing down the cost of treatment. © The Royal Society of Chemistry 2015.